2021
DOI: 10.22270/ujpr.v6i3.601
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the Aqueous Extract of Clerodendrum Thomsoniae Linn (Verbenaceae) Leaves on Type 2 Diabetic Wistar Rats Induced by the Macapos1 Type Diet and Dexamethasone

Abstract: Aim and objective: Clerodendrum thomsoniae leaves are used in Cameroon to manage diabetes and its related disorders. The study aimed at investigating the antidiabetic effect of the aqueous extract on diet and dexamethasone induced diabetic rats. Methods: Young mature leaves of C thomsoniae were dried, finely powdered and submitted to aqueous extraction. The dehydrated extract was tested in rats at 3 doses 312.5, 625 and 1250 mg/kg based on the local use of the plant. The effect of the extract on the fast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 28 publications
(21 reference statements)
0
2
0
Order By: Relevance
“…The results of the oral glucose tolerance test (OGTT) suggest that EEMP has an antihyperglycaemic effect at doses of 150 and 300 mg/kg which is similar to that of the reference drug metformin (20 mg/kg). This test suggests that EEMP acts either by slowing intestinal glucose absorption or by stimulating insulin secretion, or that this extract acts by inhibiting glucagon and/or alpha-glucosidase secretion [39].…”
Section: Discussionmentioning
confidence: 99%
“…The results of the oral glucose tolerance test (OGTT) suggest that EEMP has an antihyperglycaemic effect at doses of 150 and 300 mg/kg which is similar to that of the reference drug metformin (20 mg/kg). This test suggests that EEMP acts either by slowing intestinal glucose absorption or by stimulating insulin secretion, or that this extract acts by inhibiting glucagon and/or alpha-glucosidase secretion [39].…”
Section: Discussionmentioning
confidence: 99%
“…The dyes turn blue when H 2 O 2 oxidizes them in a mechanism mediated by peroxide reductases. However, it was found that the glucometer was acceptable for diagnosing conditions in terms of test accuracy, requiring only a drop of blood to obtain results, and being simple to use at temperatures above 95° F. It was utilized in place of the customary and drawn-out process of other diagnostic kits 23 .…”
Section: Estimation Of Oral Glucose Tolerance Testmentioning
confidence: 99%